2020
DOI: 10.1186/s12891-020-03310-5
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of finger joints using autologous rib perichondrium – an observational study at a single Centre with a median follow-up of 37 years

Abstract: Background: Gratifying long-term results are difficult to achieve when reconstructing osteoarthritic finger joints. Implant surgery is the most commonly used method to restore function and dexterity. However, all types of implant have disadvantages and may be a less favorable option in some cases, especially in young patients with a long expected lifetime and high demands on manual load. Implant related complications as loosening, instability, subsidence and stiffness are the main concerns. In this context, jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 49 publications
4
20
0
Order By: Relevance
“…4 and video 1). These results are in accordance to the recently reported longterm results (mean 37 years) after perichondrial transplantation to the PIP and MCP joints [16].…”
Section: Limitations and Strengthssupporting
confidence: 93%
See 4 more Smart Citations
“…4 and video 1). These results are in accordance to the recently reported longterm results (mean 37 years) after perichondrial transplantation to the PIP and MCP joints [16].…”
Section: Limitations and Strengthssupporting
confidence: 93%
“…The results were graded as good if pain was absent, swelling occurred only occasionally, and the range of motion was satisfactory, and such results were found in about half of the MCP and the PIP joints. Muder et al recently reported clinical outcome in 11 patients 37 years (range 34-41) after perichondrial transplantation to the PIP (n = 8) and MCP joint (n = 3) [16]. The ROM in the PIP group (n = 8) was on average 41 degrees (range 5-80).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations